PENGARUH MODEL PEMBELAJARAN LITERASI TERPADU TERHADAP PEMAHAMAN MEMBACA SISWA KELAS IV UPT SDN NO 138 INPRES MANGULABBE - M. Agus; Syahriza Azzahrah; Risnawati; Nurhusrani; Pitra Anggraini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Integrated Literacy Learning Model on fourth-grade students’ reading comprehension at UPT SDN No. 138 Inpres Mangulabbe. The study employed a quantitative approach using a pre-experimental design in the form of a one-group pretest–posttest. The research participants consisted of 13 fourth-grade students. Data were collected through a reading comprehension test administered before and after the implementation of the Integrated Literacy Learning Model. The data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test as a non-parametric statistical analysis. The results of the descriptive analysis showed an improvement in students’ reading comprehension scores. The mean pretest score was 58.15, which increased to 81.85 in the posttest, indicating a gain of 23.70 points. Furthermore, the results of the Wilcoxon Signed Rank Test revealed a significance value of p < 0.05, indicating a statistically significant difference in students’ reading comprehension before and after the implementation of the integrated literacy learning model. Based on these findings, it can be concluded that the Integrated Literacy Learning Model has a positive and significant effect on improving elementary school students’ reading comprehension. Therefore, this model is recommended as an effective instructional strategy to support reading literacy development in primary education.